Pengembangan Wisata Edukasi Berkelanjutan di Museum Geologi Bandung - Maesari, Nadhia; Suganda, Dadang; Rakhman, Cecep Ucu (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2019)
Geology Museum is a popular destination for educational tourism. But there are various obstacles so that in the implementation, educational tourism in Geological Museum has not been optimal so that need for the development of sustainable educational tourism model that can benefit both the visitors of the museum and the museum. Methods in this study using qualitative methods. Qualitative methods are used to obtain data based on factual conditions that occur, field observations, interviews and literature studies. The results in this study resulted in a new model for sustainable education in the Museum of Geology which refers to museum education policies, education and sustainable tourism indicators.